The Legitimation of Global Football Brands in the Brazilian Marketplace - Arakelian, José Sarkis; Brito, Eliane Zamith; Rosenthal, Benjamin (Internext, 2020)
Objective: This research aims to examine the institutional changes triggered by the interplay between global and local brands to advance the understanding of the legitimation process in established marketplaces. Method: Data was collected from blogs and sites of football specialists and in-depth interviews with professionals in the football business in Brazil. The analyses process was inductive inspired by Grounded Theory. Main Results: The analysis provides evidence of the legitimation of global brands in the Brazilian market, and, in contrast to expectations based on previous studies, the legitimation of local brands was maintained. Relevance/originality: Local brands maintain the legitimation and have high levels of acceptance in this social context because they are an expression of the local culture, iconic brands, and identity symbols. Theoretical/Methodological Contributions: Understanding the dynamics of a market requires the comprehension of the legitimacy process of its institutions. The contribution of this study is to discuss the effects of the destabilization provoked by the global brands’ legitimacy in local markets.